Information Technology in Tourism: Effective Strategies for Communication with Consumers - TROSHIN, Alexander Sergeevich; SOKOLOVA, Antonina Pavlovna; ERMOLAEVA, Evgeniya Olegovna; MAGOMEDOV, Ramazan Magomedovich; FOMICHEVA, Tatyana Leonidovna (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020DO - 10.14505//jemt.v11.2(42).10, 2020)
The study presents an analysis of studies on various aspects of the use of information technology in tourism. Based on an expert survey, the main directions of the development and implementation of information technologies in the field of tourism, as well as information interaction of tourism market entities using modern information technologies, are identified. A communication model is created for using modern information technologies in the tourism industry, operating in a specific system of communication interaction. The main trends in the field of electronic communications of the tourism industry are presented and recommendations for improving the effectiveness of communication strategies are developed.